Optimalisasi Efisiensi Operasional melalui Implementasi Business Process Management di Era Digital - Jeni Susyanti; Karmilaturrahman Karmilaturrahman (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The development of digital technology has encouraged companies to carry out transformations in various operational aspects. One approach that is considered effective for increasing efficiency is Business Process Management (BPM). This research aims to analyze the implementation of BPM in improving company operational efficiency in the digital era. The method used is literature study and case studies on companies that have implemented BPM. The research results show that BPM is able to provide significant efficiency through automation, standardization and monitoring of business processes. However, implementing BPM also requires organizational readiness, from structure to work culture.